#TITLE_ALTERNATIVE# - FAURIZKI RAHAYU (NIM 13204106), RHEZA
Gait analysis is a study about ability or human walking pattern. In medical discipline gait analysis is very useful to decide the best handling and therapy for medical rehabilitation. During this time medical rehabilitation doctors learn about patient walking pattern manually. Despite of that a tool at gait analysis is needed to show parameters automatically and objective for exact diagnose and the correct handling of the patient. In this experiment we did a software development for that tool. This software consists of two moduls, i.e marker detection modul and marker coordinat identification modul. In this final year project, the project is marker coordinat identification modul. The process that has done is processing the output from marker detection modul. The result of marker detection modul are random marker coordinates, so that it can get sequence changes of coordinates from each marker. The method used in this final year project is minimum displacement method. This final year project is about research for initial system of gait analysis in the case of patient human walking. This research used three markers that attached on a leg in the position x, y, z. The track that is used has 265,4 cms length and used a camera placed in the perpendicular direction to the patient track. The process is done to get more value from the gait parameters, such as tracking marker movements graph to see the human walking pattern, the changes in the angle graph, the vertical displacement of hip marker and the stride length. The analysis from data above can determine whether patients in in the normal condition or abnormal condition. This software can be used for simple gait measurement, in a condition which is the distance of marker movement is smaller than the distance of markers attached on the body. In the parameters measurement of a simple gait from the foot of two object (left or right side only), obtained pre-swing angle, vertical displacement, and the stride length. The angle of pre-swing tends to be higher if the object walks faster. The vertical displacement measurement has not been optimal for fast velocity of human walking because of the lack of the step phase data that recorded, while the measurement of the stride length is affected by the coordinates pixels to the spatial coordinates calibration. In this final year project, the accuracy of the measurement depends on the speed of the object, the accuracy of the output from the marker detection module, and the accuracy of the pixel effective value. The improvement of camera specifications, coordinates calibration procedures, and identification of important phases in walking can significantly improve the performance of gait analysis system that is designed in this final year project.